Management of Acute Pancreatitis: 'PANCREAS' Contains Eight Easy Steps to Remember the Treatment - Khaliq, Abdul; Dutta, Usha; Kochhar, Rakesh; Singh, Kartar (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: The pancreas.